ALIH AKSARA DAN ALIH BAHASA TEKS CERITA NABI NUH AS DALAM NASKAH CERITA NABI-NABI VERSI AZHARI AL-KHALIDI RAHMATULLAH - Wilda Afriani; Hasanuddin WS Hasanuddin WS; Nurizzati Nurizzati (Jurnal Bahasa dan Sastra, 2013)
The aims of this article to present the story about Nuh As in Latin script and Indonesian language, so it can be read and understood by the community and also havemessage and moral value by the community. The data of research is the  story of Nuh As,the story have another version such as from theprophets Azhari Al-Khalidi Rahmatullah written using scriptArabic-Malay and Malay language. The design of the research was descriptive research. Rather script usedrather script method andtranslation used method of translation. The results of this research is availability ofNuh text story in Latin script and Indonesian language. Rather script andtranslation done while maintaining the purity of the old language in the script basedon EYD. The storyof Nuh text tell abaout starting life Nuh and the struggle to upholdAllah Swt. religion.Based on the story of Nuh characreristic of avariety of vocabulary converting the old language​​ from this text. Through this text can also be know the language, literature and culture in the past.